NEW RESERVES OF LABOR PRODUCTIVITY IN RUSSIA - Natalia V. Gromova (Статистика и экономика)
The article describes the main problems constraining labor productivity growth in Russian economy including its technological backwardness, limitation of information technologies usage, imbalances in the structure, inefficiency of personnel labor organization and lack of their skills at workplaces. It has been sshown that the increase in labor productivity in all sectors of the Russian economy will be the basis for sustainable economic growth. Moreover, the ways of labor productivity improvement, as an interaction between government and business are suggested.